Unravelling the complexity of Direct Object Scrambling. (March 2017) - Schaeffer, Jeannette
Abstract: This study investigates the complexity of Direct Object Scrambling (DOS) by testing this phenomenon experimentally in three Dutch-speaking groups of children between the ages of 6 and 14: SLI, HFA, and TD (Specific Language Impairment, High Functioning Autism, and Typically Developing). First, the results show that, despite the failure to scramble in both pathological groups, the children with HFA do not display any morpho-syntactic deficits, whereas the children with SLI do. This suggests that the children with SLI and the children with HFA fail to scramble for different reasons. It is argued that children with SLI do this because of a problem with syntactic object placement, whereas children with HFA leave referential direct objects unscrambled because they fail to consistently integrate the different components of DOS. These results from two different pathological groups uncover different components in the complex phenomenon of DOS, at the interface of grammar (including (morpho-)syntax and semantics) and pragmatics: syntactic object placement, definiteness/referentiality, speaker/hearer beliefs, and information structure. Earlier work on DOS in younger, TD Dutch-acquiring children identifies another component of DOS, namely the pragmatic knowledge that speaker and hearer are always independent (Concept of Non-Shared Assumptions, Schaeffer, 2000). As such, the current study demonstrates the important contribution of acquisition research in TD as well as pathological populations to the unravelling and understanding of complex linguistic phenomena. Highlights: Children with High-Functioning Autism (HFA)and children with Specific Language Impairment (SLI) fail to scramble. Children with HFA do not display any morpho-syntactic deficits, whereas children with SLI do. Children with SLI: problem with syntactic object placement. Children with HFA: failure to consistently integrate grammar and pragmatics involved in Direct Object Scrambling. Acquisition research in pathological populations contributes to unravelling complex linguistic phenomena.